Polyethylene composite laminated board and preparation method thereof
By using the composite technology of ultra -high molecular weight polyethylene and shear thickened solution in polyethylene composite pressure plates, combined with polyurethane resin and thermal pressure layer complexing process, the problem of unstable shear thickened solution in protective equipment. It significantly improves the bullet resistance resistance.
Patent Information
- Application Number
- CN202411598380.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-28
AI Technical Summary
The stable combination of shear thickening liquid with protective materials in protective equipment is difficult to achieve, which affects its application in bulletproof equipment.
By preparing polyethylene composite layer pressure plates, ultra -high molecular quantitetic polyethylene continuous weftless cloth is used as a substrate, compounds with the shear thickening solution, and the combination of polyurethane resin and thermal pressure layer is used to stabilize STF and polyethylene.
It significantly improves the anti -ethylene anti -ethylene anti -bullet resistance performance of polyethylene compound layer, solves the problem of unstable shear thickened solution in the fabric, and provides a new way to improve the ballistic board's ballistic performance.
Smart Images

Figure CN119369813A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and more specifically, to a polyethylene composite laminate and a preparation method thereof. Background Art
[0002] Ultra-high molecular weight polyethylene fiber (UHMWPE), as one of the world's three major high-tech fibers, has been widely used in the field of bulletproof equipment. UHMWPE has excellent deformation resistance and energy absorption capacity. Its strength is 1.5 times that of high-quality steel, its modulus is second only to special-grade carbon fiber, its density is less than 1, and it can float on the water. In recent years, due to its better anti-ballistic performance, liquid armor composed of UHMWPE and shear thickening fluid (STF) has become the focus of current research. Impregnation with shear thickening fluid can enhance the friction of the yarn and improve the energy absorption capacity of the armor. However, the instability of the shear thickening fluid itself has limited its application. Therefore, how to stably combine the shear thickening fluid with the protective material in protective equipment is a key issue that needs to be solved urgently. Summary of the invention
[0003] The present invention is provided to solve the above problems existing in the prior art. Therefore, a polyethylene composite laminate and a preparation method thereof are needed to solve the problem of how to stably combine the shear thickening fluid with the protective material in the protective equipment.
[0004] In a first aspect, the present invention provides a method for preparing a polyethylene composite laminate, comprising:
[0005] Step 1, preparing a shear thickening liquid; wherein the shear thickening liquid comprises silica particles and polyethylene glycol;
[0006] Step 2, compounding the shear thickening liquid with a plurality of matrices to obtain a plurality of composite structures; wherein the matrix is an ultra-high molecular weight polyethylene continuous non-woven fabric;
[0007] Step 3: evenly apply a layer of polyurethane resin on the outside of each of the composite structures, and use a hot pressing lamination process to stabilize the composite to obtain a polyethylene composite laminate.
[0008] It should be noted that the polyethylene composite laminate prepared by the present invention is firstly impregnated with polyethylene by shear thickening liquid, and then a layer of Polyurethane resin glue (PU) is evenly coated on the soaked and dried fabric layer, and finally the STF and polyethylene are stably combined by hot pressing lamination technology. Compared with the prior art, the polyethylene composite laminate obtained by the present invention uses polyurethane resin and hot pressing lamination technology. The presence of polyurethane resin makes the fabric layers fit tightly together, and the hot pressing lamination technology makes the STF fill tightly between the yarns. After STF treatment, the impact energy received by the main yarn of the fabric is more transferred to the secondary yarn, and more yarns participate in energy absorption, so that the ballistic performance of the STF-impregnated fabric panel is significantly improved.
[0009] Preferably, the surface density of the ultra-high molecular weight polyethylene continuous non-woven fabric is 120 g / m 2 The number of fiber strands is 240 and the single fiber fineness is 2.5d.
[0010] It should be noted that the present invention selects the ultra-high molecular weight polyethylene continuous non-woven fabric provided by Hunan Zhongtai Special Equipment Co., Ltd., model ZH212C, which has the characteristics of high strength, high modulus and soft texture, and the surface density is 120g / m 2 The fiber strand number is 240 and the single fiber fineness is 2.5d. ZH212C is a continuous wide-width non-woven fabric of ultra-high molecular weight polyethylene, which has the characteristics of high strength, high modulus, soft texture and low specific gravity. It is made of ZTX99 series ultra-high molecular weight polyethylene fiber of Hunan Zhongtai Special Equipment Co., Ltd. The fiber density is 0.97g / m 3 , strength is 43g / d, modulus is 1600g / d, and elongation at break is 3.5%. Therefore, it has the characteristics of low elongation at break, high strength, strong impact resistance and strong cutting resistance.
[0011] Preferably, the particle size of the silicon dioxide particles is 200 nm or 500 nm.
[0012] It should be noted that the fumed silica used in the shear thickening fluid had a particle size of 20 nm and 500 nm, respectively, and was purchased from Shanghai MCC New Materials Co., Ltd. (China), polyethylene glycol with a molecular weight of 200 (PEG 200) was purchased from Wuxi Yatai United Chemical Co., Ltd. (China), and anhydrous ethanol (analytical grade) was purchased from Jiangsu Biaohui Chemical Co., Ltd. (China).
[0013] Preferably, the preparation of the shear thickening fluid comprises:
[0014] The silicon dioxide nanoparticles are mixed with anhydrous ethanol and stirred, polyethylene glycol is added for ultrasonic treatment, and the anhydrous ethanol is removed by heating to obtain a shear thickening liquid.
[0015] Preferably, the preparation of the shear thickening fluid comprises:
[0016] Silica particles with a particle size of 20 nm and 500 nm were mixed with 100 ml of ethanol respectively, and stirred for 0.5 h to obtain a first mixed solution;
[0017] Adding polyethylene glycol to the first mixed solution and stirring for 2 hours to obtain a second mixed solution;
[0018] The second mixed solution is subjected to ultrasonic treatment for 0.5 h;
[0019] After heating in a constant temperature drying oven at 90°C for 2h to remove ethanol, two types of STF were obtained, namely STF-20 and STF-500. The silica particle content in STF-20 and STF-500 was 40wt%, and the density of STF-20 was 1.42g / cm 3 , the density of STF-500 is 1.85g / cm 3 .
[0020] Preferably, after obtaining the two STFs, the method further comprises:
[0021] STF-20 and STF-500 are respectively prepared with anhydrous ethanol at a volume ratio of 1:4 to obtain STF-20 dilution and STF-500 dilution, and the STF-20 dilution or STF-500 dilution is used as a shear thickening liquid compounded with a matrix.
[0022] Preferably, the shear thickening liquid is compounded with a plurality of matrices to obtain a plurality of composite structures, including:
[0023] The multiple substrates were immersed in the STF-20 dilution solution or the STF-500 dilution solution for 0.5 h, the excess shear thickening liquid was removed, and the substrates were convection dried in a constant temperature environment to remove the ethanol, thereby obtaining multiple composite structures.
[0024] Preferably, a layer of polyurethane resin is evenly applied on the outer side of each of the composite structures, and a hot pressing lamination process is used to stably laminate the composite structure to obtain a polyethylene composite laminate, comprising:
[0025] Apply a layer of polyurethane resin to each of the composite structures, and convection dry them in a 60° forced air drying oven for 0.5 h to obtain a plurality of fabrics;
[0026] The fabrics were stacked in a set order, tightly wrapped with polyester film and placed in a hot press, centered on all four sides; the mold was heated to 125° for 1 hour, and maintained at 5MPa, 12MPa, and 18MPa pressures for 10 minutes, respectively, and finally the pressure was increased to 24MPa, maintained for 40 minutes, then cooled to 30°, the pressure was released and the plate was taken out to obtain a polyethylene composite laminate.
[0027] In a second aspect, the present invention provides a polyethylene composite laminate prepared by the preparation method described above.
[0028] The present invention has at least the following beneficial effects:
[0029] The present invention utilizes a hybrid preparation scheme of impregnating polyethylene fabrics with different shear thickening liquids, and through the selection of the matrix and the impregnation liquid, in combination with an innovatively designed lamination process, the prepared polyethylene composite laminate has significantly improved anti-ballistic performance compared with traditional bulletproof materials, and solves the problem of instability of the shear thickening liquid in the fabric. This also provides a new application approach for using shear thickening liquids to improve the ballistic performance of bulletproof plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention provides a flowchart of a method for preparing a polyethylene composite laminate.
[0031] Figure 2 A schematic diagram of a ballistic testing device provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and specific embodiments, but are not intended to limit the present invention. For the various steps described herein, if there is no necessity for a causal relationship between each other, the order in which they are described as examples herein should not be regarded as a limitation, and those skilled in the art should know that they can be adjusted in order, as long as the logic between them is not destroyed, resulting in the inability to implement the entire process.
[0033] The present invention provides a method for preparing a polyethylene composite laminate. Figure 1 As shown in the figure, the preparation method uses ultra-high molecular weight polyethylene continuous non-woven fabric as the matrix, combines it with STF based on hot pressing molding, and proposes four different composite laminate preparation schemes. Figure 1 shown.
[0034] Information on four different polyethylene composite laminates is recorded in Table 1. For all composite laminates, "P" indicates aramid III fabric; the number after "P" indicates the number of fabric layers; "N" and "S" indicate whether the fabric layer is impregnated with STF; the number after "S" indicates the silica particle size. Details are shown in the table below:
[0035] Table 1 Composite laminate parameters
[0036]
[0037] Embodiment 1:
[0038] A P20S (20) polyethylene composite laminate is prepared, the preparation method comprising:
[0039] Step 1. Prepare a shear thickening fluid with a density of 1.42 g / cm3 (STF-20).
[0040] First, a certain amount of 20nm silica particles was mixed with 100ml of ethanol and stirred for 0.5h using a force-enhancing stirrer; then a certain amount of polyethylene glycol with a molecular weight of 200 was added to the solution and stirred for 2h. Then, an ultrasonic cleaner was used to perform ultrasonic treatment on the solution for 0.5h. Finally, the solution was heated in a constant temperature drying oven at 90°C for 2h to remove the ethanol, and STF-20 with a silica particle content of 40wt% was obtained.
[0041] Step 2. Compounding the shear thickening liquid with the polyethylene fabric.
[0042] The ultra-high molecular weight polyethylene continuous non-woven fabric is divided into fabrics with a size of 200 mm×200 mm, and the groups are numbered and weighed. The weight of the nth group of pure fabric is recorded as ng, and n is a maximum of 20.
[0043] In order to make the STF completely penetrate the fabric, the prepared STF was diluted with anhydrous ethanol, wherein the volume ratio of STF to ethanol was 1:4, and a diluent was prepared.
[0044] The grouped fabrics were immersed in the diluted solution for 0.5 h, and then rolled with a 1.5 kg roller to remove excess STF. Finally, the treated fabrics were convection dried in a 60° C. constant temperature drying oven for 1.5 h to remove ethanol.
[0045] Step 3. Heat-pressing lamination process for stable compounding.
[0046] First, a layer of Polyurethane resin glue (PU) is evenly applied to the soaked and dried fabric layer, and convection dried in a 60° forced air drying oven for 0.5 h. Then, the fabric layers are stacked, tightly wrapped with polyester film and placed in a press, with the four sides centered. The mold is heated to 125° for 1 h, and maintained at 5 MPa, 12 MPa, and 18 MPa pressures for 10 minutes, respectively. Finally, the pressure is increased to 24 MPa, maintained for 40 minutes, and then cooled to 30° to release the pressure and take out the plate, thereby obtaining a P20S (20) polyethylene composite laminate.
[0047] Embodiment 2:
[0048] A P20S (500) polyethylene composite laminate is prepared, the preparation method comprising:
[0049] Step 1. Prepare a shear thickening fluid with a density of 1.85 g / cm3 (STF-500).
[0050] First, a certain amount of 500nm silica particles was mixed with 100ml ethanol and stirred for 0.5h using a force-enhancing stirrer; then a certain amount of polyethylene glycol with a molecular weight of 200 was added to the solution and stirred for 2h. Then, an ultrasonic cleaner was used to perform ultrasonic treatment on the solution for 0.5h. Finally, the solution was heated in a constant temperature drying oven at 90°C for 2h to remove the ethanol, and STF-500 with a silica particle content of 40wt% was obtained.
[0051] Step 2. Compounding the shear thickening liquid with the polyethylene fabric.
[0052] The aramid III fabric is divided into fabrics of size 200mm×200mm, and the groups are numbered and weighed. The weight of the nth group of pure fabric is recorded as ng, and the maximum value of n is 20.
[0053] In order to make the STF completely penetrate the fabric, the STF prepared above was diluted with anhydrous ethanol, wherein the volume ratio of STF to ethanol was 1:4, and a diluent was prepared.
[0054] The grouped fabrics were immersed in the diluted solution for 0.5 h, and then rolled with a 1.5 kg roller to remove excess STF. Finally, the treated fabrics were convection dried in a 60° C. constant temperature drying oven for 1.5 h to remove ethanol.
[0055] Step 3. Heat-pressing lamination process for stable compounding.
[0056] Firstly, a layer of Polyurethane resin glue (PU) is evenly applied to the soaked and dried fabric, and then convection dried in a 60° forced air drying oven for 0.5 h; then, the fabrics are stacked, tightly wrapped with polyester film and placed in a press, with the four sides centered; the mold is closed and heated to 125° for 1 h, and maintained at 5 MPa, 12 MPa, and 18 MPa pressures for 10 minutes respectively, and finally the pressure is increased to 24 MPa and maintained for 40 minutes, then the temperature is lowered to 30°, the pressure is released, and the plate is taken out to obtain a P20S (500) polyethylene composite laminate.
[0057] Example 3
[0058] A P10S (20) + P10S (500) polyethylene composite laminate is prepared, and the preparation method comprises:
[0059] Step 1. Compounding the shear thickening fluid with the polyethylene fabric.
[0060] The two shear thickening fluids STF-20 and STF-500 prepared in Examples 2 and 3 were respectively mixed with anhydrous ethanol at a volume ratio of 1:4 to prepare diluents to obtain STF-20 diluent and STF-500 diluent.
[0061] The fabrics with group numbers 1-10 were soaked in STF-20 dilution for 0.5 h, and the fabrics with group numbers 11-20 were soaked in STF-500 dilution for 0.5 h, and then rolled with a roller weighing 1.5 kg to remove excess STF. Finally, the treated fabrics were convection dried in a constant temperature drying oven at 60°C for 1 h to remove ethanol.
[0062] Step 2. Hot pressing lamination process to stabilize the composite.
[0063] Firstly, a layer of Polyurethane resin glue (PU) is evenly applied to the soaked and dried fabric, and then convection dried in a 60° forced air drying oven for 0.5 h. Then, the fabrics are stacked in the order of group numbers, tightly wrapped with polyester film and placed in a press, with the four sides centered. The mold is heated to 125° for 1 h, and maintained at 5 MPa, 12 MPa, and 18 MPa pressures for 10 minutes respectively. Finally, the pressure is increased to 24 MPa, maintained for 40 minutes, and then cooled to 30° to release the pressure and take out the plate, thereby obtaining a P10S (20) + P10S (500) polyethylene composite laminate.
[0064] Example 4
[0065] A P10S (500) + P10S (20) polyethylene composite laminate is prepared, and the preparation method comprises:
[0066] Step 1. Compounding the shear thickening fluid with the polyethylene fabric.
[0067] The aramid fabric was completely soaked in the STF-20 dilution solution and the STF-500 dilution solution prepared in the above embodiment 3.
[0068] First, the fabrics with group numbers 1-10 were soaked in STF-500 dilution for 0.5 h, and the fabrics with group numbers 11-20 were soaked in STF-20 dilution for 0.5 h, and then rolled with a 1.5 kg roller to remove excess STF. Finally, the treated fabrics were convection dried in a constant temperature drying oven at 60°C for 1 h to remove ethanol.
[0069] Step 2. Hot pressing lamination process to stabilize the composite.
[0070] Firstly, a layer of Polyurethane resin glue (PU) is evenly applied to the soaked and dried fabric, and then convection dried in a 60° forced air drying oven for 0.5 h. Then, the fabrics are stacked in the order of group numbers, tightly wrapped with polyester film and placed in a press, with the four sides centered. The mold is heated to 125° for 1 h, and maintained at 5 MPa, 12 MPa, and 18 MPa pressures for 10 minutes respectively. Finally, the pressure is increased to 24 MPa, maintained for 40 minutes, and then cooled to 30° to release the pressure and take out the plate, thereby obtaining a P10S (500) + P10S (20) polyethylene composite laminate.
[0071] Embodiment 5:
[0072] Ballistic impact test.
[0073] The four polyethylene composite laminates and a group of pure polyethylene fabric panels prepared in the above four embodiments were used as bulletproof panels and ballistic impact tests were carried out using a two-stage light gas gun. The ballistic test device used is as follows: Figure 2 shown.
[0074] N2 was used as the working gas in this test, and the pressure in the high-pressure chamber was controlled at 1 MPa in each test. This test used a small steel core projectile with a diameter of 9 mm and a mass of 3.05 g to test laminates of different hybrid configurations. An oscilloscope was used to measure the incident velocity, and a sky-type velocimeter was used to measure the residual velocity. The energy absorbed by the laminate during penetration can be calculated from the initial velocity and the residual velocity.
[0075] The ballistic impact test data is shown in Table 2:
[0076] Table 2 Ballistic impact data table
[0077]
[0078] The energy absorption and energy absorption rate of the laminates show a step distribution of "pure UHMEPE laminates - UHMWPE laminates impregnated with a single shear thickening liquid - hybrid laminates impregnated with a shear thickening liquid", among which the hybrid laminates have the strongest energy absorption capacity, the highest energy absorption rate, and the best impact resistance; while the pure UHMWPE laminates have the worst energy absorption capacity, the lowest energy absorption rate, and the worst impact resistance. Compared with pure UHMWPE laminates, the energy absorbed by the laminates impregnated with a single shear thickening liquid increased by 4.8%, and the energy absorption rate increased by 5%. This shows that the impact resistance of the UHMWPE laminates has been enhanced after impregnation with the shear thickening liquid. After the hybrid configuration, the energy absorption capacity of the laminates is further enhanced, the absorbed energy increased by 11.5%, and the energy absorption rate increased by more than 10%. This also shows that the hybrid configuration is effective in improving the impact resistance of the laminates. Among them, the hybrid laminates with a 500nm+20nm configuration absorb the most energy, which may be due to the higher incident velocity of this combination.
[0079] The back deformation depth of pure UHMWPE laminate is the largest, while the back deformation depth of laminate impregnated with single shear thickening liquid and hybrid laminate impregnated with shear thickening liquid is not much different. The thickness of pure UHMWPE laminate is 4.23mm, and the average thickness of laminate impregnated with shear thickening liquid is 5.50mm. The deformation degree of pure UHMWPE laminate reaches 278.72%, while the deformation degree of laminate impregnated with shear thickening liquid is maintained between 130% and 145%. Compared with pure UHMWPE, the back deformation degree of laminate impregnated with shear thickening liquid is reduced by at least 135%, which shows that impregnation with shear thickening liquid can effectively enhance the deformation resistance of UHMWPE laminate.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a polyethylene composite laminate, characterized in that: include: Step 1, preparing a shear thickening fluid; wherein the shear thickening fluid (STF) comprises silica particles and polyethylene glycol; Step 2, compounding the shear thickening liquid with a plurality of matrices to obtain a plurality of composite structures; wherein the matrix is an ultra-high molecular weight polyethylene continuous non-woven fabric; Step 3: evenly apply a layer of polyurethane resin on the outside of each composite structure, and use a hot pressing lamination process to stabilize the composite to obtain a polyethylene composite laminate.
2. The preparation method according to claim 1, characterized in that: The surface density of the ultra-high molecular weight polyethylene continuous non-woven fabric is 120g / m 2 The number of fiber strands is 240 and the single fiber fineness is 2.5d.
3. The preparation method according to claim 1, characterized in that: The particle size of the silicon dioxide particles is 20 nm or 500 nm.
4. The preparation method according to claim 1, characterized in that: The method for preparing the shear thickening fluid comprises: The silicon dioxide nanoparticles are mixed with anhydrous ethanol and stirred, polyethylene glycol is added for ultrasonic treatment, and the anhydrous ethanol is removed by heating to obtain a shear thickening liquid.
5. The preparation method according to claim 1, characterized in that: The method for preparing the shear thickening fluid comprises: Silica particles with a particle size of 20 nm and 500 nm were mixed with 100 ml of ethanol respectively, and stirred for 0.5 h to obtain a first mixed solution; Adding polyethylene glycol to the first mixed solution and stirring for 2 hours to obtain a second mixed solution; The second mixed solution is subjected to ultrasonic treatment for 0.5 h; After heating in a constant temperature drying oven at 90°C for 2 h to remove ethanol, two shear thickening fluids were obtained, namely STF-20 and STF-500. The silica particle content in STF-20 and STF-500 was 40 wt%, and the density of STF-20 was 1.42 g / cm 3 , the density of STF-500 is 1.85g / cm 3 .
6. The method according to claim 5, characterized in that After obtaining the two STFs, the method further includes: STF-20 and STF-500 are respectively prepared with anhydrous ethanol at a volume ratio of 1:4 to obtain STF-20 dilution and STF-500 dilution, and the STF-20 dilution or STF-500 dilution is used as a shear thickening liquid compounded with a matrix.
7. The method according to claim 6, characterized in that The shear thickening liquid is compounded with a plurality of matrices to obtain a plurality of composite structures, including: The multiple substrates were immersed in the STF-20 dilution solution or the STF-500 dilution solution for 0.5 h, the excess shear thickening liquid was removed, and the substrates were convection dried in a constant temperature environment to remove the ethanol, thereby obtaining multiple composite structures.
8. The method according to claim 7, characterized in that A layer of polyurethane resin is evenly applied on the outer side of each composite structure, and a hot pressing lamination process is used to stably laminate the composite structure to obtain a polyethylene composite laminate, including: Apply a layer of polyurethane resin to each of the composite structures, and convection dry them in a 60° forced air drying oven for 0.5 h to obtain a plurality of fabrics; The fabrics were stacked in a set order, tightly wrapped with polyester film and placed in a hot press, centered on all four sides; the mold was heated to 125° for 1 hour, and maintained at 5MPa, 12MPa, and 18MPa pressures for 10 minutes, respectively, and finally the pressure was increased to 24MPa, maintained for 40 minutes, then cooled to 30°, the pressure was released and the plate was taken out to obtain a polyethylene composite laminate.
9. A polyethylene composite laminate prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Novel bulletproof material and body armor
CN109141121A
Flexible protective composite material and manufacturing method thereof
CN112900105A
Preparation method of silicon dioxide / ultra-high molecular weight polyethylene non-woven cloth
CN114318858A
Aramid fiber composite laminated board as well as preparation method and application thereof
CN118238489A
Impact resistant, torsion-reducing protective athletic gear using shear thickening fluid
US20110283433A1